2020
DOI: 10.1007/s00266-020-01827-7
|View full text |Cite
|
Sign up to set email alerts
|

Human Histology and Persistence of Various Injectable Filler Substances for Soft Tissue Augmentation

Abstract: An increasing number of soft tissue filler substances have been introduced to the beauty market outside the U.S. which lack experimental and clinical data in support of their claim. Ten commercially available filler substances were examined for biocompatibility and durability: 0.1 cc of each substance was injected deep intradermally into the volar forearm of one of the authors and observed for clinical reaction and permanence. At 1, 3, 6, and 9 months the test sites were excised, histologically examined, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 45 publications
2
43
1
Order By: Relevance
“…At the sites where the PLLA was administered, a weak inflammatory reaction, infiltration of foreign body giant cells, and elongated fibroblasts were observed, which are presumed to be the central mechanistic features 4 . Type I collagen statistically and significantly increased from baseline to 6 months after PLLA injection in human skin 7,8 . Moreover, the clinically volume-augmenting effect of PLLA could be confirmed even within one month after injection, which is much faster than the rate reported in an- other study 8 .…”
Section: Dear Editormentioning
confidence: 92%
“…At the sites where the PLLA was administered, a weak inflammatory reaction, infiltration of foreign body giant cells, and elongated fibroblasts were observed, which are presumed to be the central mechanistic features 4 . Type I collagen statistically and significantly increased from baseline to 6 months after PLLA injection in human skin 7,8 . Moreover, the clinically volume-augmenting effect of PLLA could be confirmed even within one month after injection, which is much faster than the rate reported in an- other study 8 .…”
Section: Dear Editormentioning
confidence: 92%
“…Although hyaluronic acid and collagen-based gels are available soft-tissue filler for filling subcutaneous voids in clinics, these materials fail to stimulate adipose regeneration and often suffer from limited longevity due to rapid resorption in vivo. 66,67 Our results suggested that future soft-tissue filler materials could incorporate DAT elements in order to restore the adipose deficits instead of simply filling them with static materials. Since the present study demonstrated that SDAT and VDAT have different mechanical stiffness, they could serve as available substitutes for filling soft-tissue defects that require various stiffness.…”
Section: Discussionmentioning
confidence: 71%
“…However, the problem of granuloma formation needs to be solved. Bellafill, being a third generation PMMA filler following Artefill and Artecol, was developed to avert the complication of granuloma formation, with 3 major improvements, namely (i) uniform microspheres sized above 20 microns, thereby preventing them from being phagocytosed by macrophages, [5][6][7][8] (ii) lack of irregular surfaces mitigates inflammatory foreign body reaction, (iii) clumping of microspheres is prevented by fixation in a suspension of viscous collagen, allowing for even collagenesis. A 5-year study on the safety of Bellafill in nasolabial fold augmentation showed a 1.7% incidence of granuloma formation.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Aggregation of microspheres is prevented by fixation in a suspension of viscous collagen, allowing for even collagenesis around the microspheres. 5,8 Bellafill provides an immediate volumizing effect due to the bovine collagen which will be absorbed over a month. This is followed by permanent volumization through collagenesis induced by the PMMA microspheres.…”
Section: Introductionmentioning
confidence: 99%